Pengaruh Struktur Modal, Likuiditas, Dan Ukuran Perusahaan Terhadap Kinerja Keuangan Pada PT. Waskita Karya (Persero), Tbk Periode 2015-2024 - Putriani Putriani; Faisal Faisal (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
This study aims to analyze the effect of Debt to Equity Ratio (DER), Current Ratio (CR), and Company Size on Financial Performance at PT Waskita Karya (Persero) Tbk for the 2015-2024 period. This study uses a descriptive method with a quantitative approach. The data used are secondary data obtained from the company’s financial statements during the study include descriptive stastistical analysis, classical assumption tests, multipe linear regression analysis, correlation coefficients, coefficients of determination, and hypothesis testing using t-tests and f-tests using SPSS version 26. The results indicate that the Debt to Equity Ratio (DER) partially has a significant negative effect on Financial Performance with a significance value of 0.088 < 0.5 and t-value > t-table (|-3.487| > 2.051). Meanwhile, the Current Ratio (CR) did not significantly influence Financial Performance, with a significance value of 0.218 > 0.05 and a calculated t-value < t-table (|1.388| < 2.051). Similarly, Company Size did not significantly influence Financial Performance, with a significance value of 0.434 > 0.05 and a calculated t-value < t-table (|-0.823| < 2.051). Simultaneously, Debt to Equity Ratio (DER), Current Ratio (CR), And Company Size did not significantly influeence Financial Performance, with a significance value of 0.059 > 0.05 and a calculated f-value > f-table (|4.375| > 4.07).